2020
DOI: 10.1177/0003134820960078
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Understanding and Compliance Among Surgical Patients in Low-Income Urban Teaching Hospitals

Abstract: Financial and educational barriers significantly impact low socioeconomic status racial and ethnic minority groups in their pursuit of health care, though less is known about the interplay of these factors in the pursuit of surgical care. This study was designed to uncover the challenges to patient understanding and compliance with pre- and postsurgical clinical advice in low-income urban environments. The data for this study were collected in spoken survey with eighty patients in 9 surgery clinics at Temple U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…[35][36][37] One study examining a surgical population found that experiences with physicians, communication, finances, social resources, and individual agency impact patient compliance in low-income urban hospitals. 37 Health care institutions, community-based organizations, and providers must acknowledge how these barriers impact patient access to care, and should adopt patientcentered strategies such as easing transportation barriers, reducing wait times, and creating a welcoming environment to intentionally decrease the instances of MCOs. [38][39][40] Previous studies assessing the impact of no-show appointments on the healthcare system found that noshow appointments negatively impact cost, revenue, and use of resources in healthcare systems, as well as decrease provider and clinic productivity, efficiency, and capacity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[35][36][37] One study examining a surgical population found that experiences with physicians, communication, finances, social resources, and individual agency impact patient compliance in low-income urban hospitals. 37 Health care institutions, community-based organizations, and providers must acknowledge how these barriers impact patient access to care, and should adopt patientcentered strategies such as easing transportation barriers, reducing wait times, and creating a welcoming environment to intentionally decrease the instances of MCOs. [38][39][40] Previous studies assessing the impact of no-show appointments on the healthcare system found that noshow appointments negatively impact cost, revenue, and use of resources in healthcare systems, as well as decrease provider and clinic productivity, efficiency, and capacity.…”
Section: Discussionmentioning
confidence: 99%
“…35–37 One study examining a surgical population found that experiences with physicians, communication, finances, social resources, and individual agency impact patient compliance in low-income urban hospitals. 37 Health care institutions, community-based organizations, and providers must acknowledge how these barriers impact patient access to care, and should adopt patient-centered strategies such as easing transportation barriers, reducing wait times, and creating a welcoming environment to intentionally decrease the instances of MCOs. 38–40…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that economic income is a factor affecting patient compliance 19 . Coats et al 30 found that financial accessibility and acceptance were inversely correlated with treatment abandonment, i.e., the higher income means better compliance, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In the state of arts, surgery compliance is regarded as a key factor to the prognosis of various diseases 15 17 , and thus becomes the focus of social healthcare research 18 , 19 . It is non-negligible that SO rarely happens, according to the clinical statistics.…”
Section: Introductionmentioning
confidence: 99%